Formulasi dan Uji Mutu Fisik Sediaan Hand Cream Ekstrak Kulit Ubi Jalar Kuning (Ipomoea batatas L.) - Safitri, Cikra Ikhda Nur; Pristya, Putri Firnabila (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to evaluate the potential of yellow sweet potato skin extract as an active ingredient in topical hand cream preparations and to analyze the physical characteristics of the preparation. Extraction of active substances is carried out through a maceration process with 70% ethanol solvent for 3 days to obtain optimal extract from sweet potato skin. The hand cream formulation uses two concentrations of sweet potato skin extract, namely 2% and 4%, which are tested with several physical quality parameters. Organoleptic testing shows that the hand cream is soft, easily absorbed, and homogeneous. The pH test results had an average of 5.5 in all three replications, the viscosity in non-concentration showed results of 9381 mPas, F1 15976 mPas, and F2 19618 mPas, and the spreadability showed 5.3 in all three replications. The conclusion of this study is that the formulation of yellow sweet potato skin extract shows good physical characteristics or is considered to meet SNI standards. The implications of these results indicate that yellow sweet potato skin extract can be developed as a promising natural active ingredient in the formulation of skin care products, especially hand cream.